Pengaruh Efisiensi Operasional, Dana Pihak Ketiga dan Likuiditas Terhadap Profitabilitas Pada Lembaga Perkreditan Desa (LPD) Se-Kecamatan Blahbatuh Kabupaten Gianyar - Ni Putu Indira Sari Dewi; I. B. Made Putra Manuaba (Universitas Warmadewa, 2026)
The return on assets of LPDs in Blahbatuh Regency subsequently declined. This indicates a decline in LPD profit performance, requiring LPD management to evaluate its strategic policies to improve future performance. The research aims to empirically demonstrate the influence of operational efficiency, third-party financing, and liquidity on LPD profitability in Blahbatuh District, Gianyar Regency. The research method employed in this study was saturated sampling. This type of data utilized quantitative data and secondary data sources. The data collection method employed literature studies and data analysis techniques using multiple linear regression tests. The research results show that operational efficiency negatively impacts LPD profitability in Blahbatuh District, Gianyar Regency. Third-party funds and liquidity positively impact LPD profitability in Blahbatuh District, Gianyar Regency.